The Impact of The Human Development Index and Economic Poverty in Sorong City Southwest Papua 2010-2024 - May Husnul Khotimah; M. Yusril Khalik (Jurusan Ilmu Ekonomi Fakultas Ekonomi Universitas Trunojoyo Madura, 2026)
and economic growth on poverty levels in Sorong City, Southwest Papua Province, from 2010 to 2024. This research employs a quantitative approach using ordinary least squares (OLS) regression. The analysis results indicate that the HDI has a positive but insignificant effect on poverty. Meanwhile, economic growth has a positive and significant effect on poverty. Simultaneously, all independent variables can explain the variation in the dependent variable. These findings suggest that a corresponding reduction in poverty has not accompanied ongoing Development and economic growth. Therefore, the results of this study are expected to serve as a basis for the Sorong City government in formulating poverty alleviation policies that consider both the quality of human Development and the equitable distribution of the benefits of economic growth. The limitation of this study lies in the number of variables used, which does not yet fully reflect the complexity of socioeconomic factors influencing poverty. Keyword: Economic Growth, Human Development Index (HDI), Poverty